2019
DOI: 10.18410/jebmh/2019/662
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cervical Cytology Using PAP Smear in Women Residing in Bangalore Rural, India

Abstract: BACKGROUND Cervical cancer is one of the most deadly and common forms of cancer among women, worldwide. This disease could is preventable, by detecting it using Pap screening test. The objective of this study was to determine the pattern of various cervical smear abnormalities and to study the prevalence of epithelial cell abnormalities in our study population. METHODS A total of 200 married women between 21-70 years of age were enrolled in the study. Pap smear was done by the conventional method and reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…In the present study, most (22, 34.92%) of the abnormal cytology was detected in patients in the age group between 41 and 50 years (Table 4), with a mean age of 45.5 years, similar to other studies 2 . This study revealed ASCUS 51(3.27%) to be the most common ECA, which was similar to those obtained in other studies 3,4,8,14 (Table 5).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, most (22, 34.92%) of the abnormal cytology was detected in patients in the age group between 41 and 50 years (Table 4), with a mean age of 45.5 years, similar to other studies 2 . This study revealed ASCUS 51(3.27%) to be the most common ECA, which was similar to those obtained in other studies 3,4,8,14 (Table 5).…”
Section: Resultssupporting
confidence: 92%
“…There were 1,499 (95.97%) cases of NILM, with the most common lesion 1,149 (72%) being of non-specific inflammation, similar to studies by others 2,4 . The ECA was detected in 4.04% of the cases, comparable to the ECA detection rates of 0.5% and 8.48% in various studies [2][3][4]7,8,11,14 (Table 3). In the present study, most (22, 34.92%) of the abnormal cytology was detected in patients in the age group between 41 and 50 years (Table 4), with a mean age of 45.5 years, similar to other studies 2 .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation